2018
DOI: 10.1177/0309524x18791390
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of aerodynamic flow around H-Darrieus rotor with camber-bladed profile

Abstract: Improving the H-Darrieus rotor is often followed by the investigation of the influence of the turbine’s parameter design, notably, the aspect ratio, the solidity ( σ), the tip speed ratio, and the airfoil profile shape. In this work, we are interested in both the aerodynamic flows around a straight cambered blade profile and the rotor turbine wake separation of a Darrieus vertical axis wind turbine. The aim of this study is to better understand the evolution of the instantaneous torque and the generated-separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Some works relate these detachments, the vortex generation, with the values of C P the rotor power coefficient for different angles. Qamar and Janajreh (2017) and Souaissa et al (2019) model Darrieus using CFD and although the behavior differs in some aspects, it is corroborated that the minimum values of C P corresponds to the highest vortex shedding zone. Bianchini et al (2017) also shows CFD results and comparisons with wake experiments for a three-bladed Darrieus rotor.…”
Section: Fluid-rotor Interaction Analysismentioning
confidence: 71%
“…Some works relate these detachments, the vortex generation, with the values of C P the rotor power coefficient for different angles. Qamar and Janajreh (2017) and Souaissa et al (2019) model Darrieus using CFD and although the behavior differs in some aspects, it is corroborated that the minimum values of C P corresponds to the highest vortex shedding zone. Bianchini et al (2017) also shows CFD results and comparisons with wake experiments for a three-bladed Darrieus rotor.…”
Section: Fluid-rotor Interaction Analysismentioning
confidence: 71%
“…This behavior is particularly relied upon by the use of a cambered airfoil profile. 31 Thus, in these regions, resistive torque has been generated that prevents the rotor from starting.
Figure 9.Total torque coefficient at different operating TSRs: (a) instantaneous, (b) average.
…”
Section: Resultsmentioning
confidence: 99%
“…The blades are profiled with a cambered airfoil NACA4312 that allows better self-starting capabilities. 26 The main geometrical features of the H-Darrieus are reported in Table 1.…”
Section: Geometrical H-darrieus Modelsmentioning
confidence: 99%
“…Mendoza et al [19] compared the wake of HAWTs and VAWTs in the atmospheric boundary layer with different surface roughness of terrain. Souaissa et al [20] focused on flows around a cambered blade profile and confirmed that the instantaneous torque is highly related to generated-separated blade vortex. Some innovative designs of VAWTs have been proposed in previous literature, and flow fields of these novel designs have been studied, too.…”
Section: Introductionmentioning
confidence: 93%